Certification of reference materials of sodium tartrate dihydrate and potassium citric monohydrate for water content. Issue 13 (16th March 2016) - Liu, Wei; Wang, Haifeng; Gu, Xifeng; Quan, Can; Dai, Xinhua
Abstract : CRMs for water content in solids were used to calibrate Karl Fischer titrators or validate the measurement method for the accuracy and consistency of results. Abstract : Certified reference materials (CRMs) for the determination of the water content of solids have been used to calibrate Karl Fischer titrators and to validate the measurement method for the accuracy and consistency of results. In the present study, CRMs of sodium tartrate dihydrate and potassium citrate monohydrate for the determination of water content were investigated and certified. The stability of water content against humidity, the thermal stability and the composition of substances evaporated on drying of the CRMs candidates were characterized. A mass balance approach based on mass loss on drying was investigated to measure their water content. Karl Fischer coulometric and volumetric titrations were improved, especially the sampling method, and were utilized to certify the two CRMs. The certified water content and its expanded uncertainty for the two CRMs were found to be 156.3 mg g −1 (1.3 mg g −1, k = 2) and 55.8 mg g −1 (0.6 mg g −1, k = 2), respectively.